Potential factors affecting free base nicotine yield in electronic cigarette aerosols. (3rd July 2021) - Gholap, Vinit V.; Pearcy, Adam C.; Halquist, Matthew S.
ABSTRACT: Background: The free base and protonated nicotine forms in e-cigarette aerosol have shown different absorption profiles in users. Therefore, it is also important to identify the factors which can affect the ratio of these nicotine forms in the aerosol. Such factors may include nicotine concentrations, flavors, PG:VG ratios, types of nicotine chemical compounds and e-cigarette battery power outputs. The current study attempts to identify such factors using a controlled experiment. Research designs and methods: The aerosol was generated using validated aerosol generating model. Various factors were tested for their effect on nicotine forms. Additionally, a degradation study of one of the nicotine compounds, nicotine salicylate, was also carried out using mass spectrometry. Results: The free base nicotine in the aerosol was found to be affected by flavors, battery power output, nicotine compound type and PG:VG ratios. Based on the preliminary mass spectrometry data, degradation of nicotine salicylate was found to be one of the significant factors affecting free base nicotine in aerosol. Conclusions: Potential factors affecting free base nicotine in e-cigarette aerosol have been identified in this study. These findings would help in understanding the nicotine delivery better and assist for better regulations.